5. Multidisciplinary Collaboration Through Learning Communities: Navigating Anxiety - Erin DeLathouwer; Wendy Roy; Ann Martin; Jasmine Liska (Collected Essays on Learning and Teaching, 2012)
A problem common to university faculty and students is an implicit sense of inadequacy regarding institutional hierarchies and disciplinary boundaries. Through a focus on multidisciplinarity, learning communities enable members to navigate multiple points of view within, between, and beyond apparent institutional boundaries. After having led a workshop that placed participants in the positions of both students and faculty members negotiating multidisciplinarity through learning communities, we conclude that learning communities’ methodological leveling of traditional hierarchies implicit in higher education leads to a sense of belonging that enables students and faculty to take risks essential for authentic learning. Anxiety over participation in academic discussions both inside and outside the classroom, and from within and beyond one’s disciplinary expertise, thus becomes productive rather than debilitating.